1988
DOI: 10.1080/08940630.1988.10466349
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function and Symptom Responses after 6.6-Hour Exposure to 0.12 ppm Ozone with Moderate Exercise

Abstract: JAPCAPublication details, including instructions for authors and subscription information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 20 publications
3
112
1
3
Order By: Relevance
“…Epidemiological studies have found associations between low ozone levels and: 1) decline in pulmonary functions (Galizia and Kinney, 1999;Folinbee et al, 1988;Kinney et al, 1996;Devlin et al, 1991); 2) increase in hospital admissions for asthma, especially among children (Stern et al, 1994;Galizia and Kinney, 1999); and 3) congestive heart failure among the elderly (Burnett et al, 1997b). Positive associations between short-term 1-hour max ozone levels and mortality, adjusted for the potential confounding effects of other pollutants and weather, have been found in Los Angeles and New York (Kinney and Ozkaynak, 1991;Kinney et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have found associations between low ozone levels and: 1) decline in pulmonary functions (Galizia and Kinney, 1999;Folinbee et al, 1988;Kinney et al, 1996;Devlin et al, 1991); 2) increase in hospital admissions for asthma, especially among children (Stern et al, 1994;Galizia and Kinney, 1999); and 3) congestive heart failure among the elderly (Burnett et al, 1997b). Positive associations between short-term 1-hour max ozone levels and mortality, adjusted for the potential confounding effects of other pollutants and weather, have been found in Los Angeles and New York (Kinney and Ozkaynak, 1991;Kinney et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The health effects associated with short-term exposure to ambient ozone are well documented in air pollution studies (Galizia and Kinney, 1999;Devlin et al, 1991;Folinbee et al, 1988;Kinney et al, 1996;Stern et al, 1994;Levy et al, 2001;Kelsall et al, 1997;Moolgavkar, 2000;Thurston and Ito, 2001;Glodberg et al, 2001). Exposure to ozone levels less than 100ppb can irritate the respiratory tract, particularly for sensitive populations, concentrations above 300ppb can cause nose and throat irritation, and levels above 1000ppb (typical levels in very smoggy air) can cause breathing problems and headaches.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled clinical studies have demonstrated that decrements in forced expiratory volume in 1 sec (FEV1), occurred in healthy, exercising adults exposed to ozone concentrations of 0.080 to 0.12 ppm for up to 6.6 hr (6)(7)(8). When asthmatics and healthy individuals were exposed solely to ozone, changes in respiratory function were similar (9), but asthmatics who were exposed to ozone and then challenged with an allergen had a greater response than a control group (10).…”
Section: Introductionmentioning
confidence: 94%
“…Of particular health significance is the TSP component of air pollution, which is itself a complex mixture (54). Acute adverse respiratory effects of ozone exposure are also well documented in animal and human populations (55)(56)(57).…”
Section: Quality Oflifementioning
confidence: 99%